ESTIMATION OF STUDENTS HIGH MATHEMATICAL ABILITY IN SOLVING COUNTING PLOBLEMS - Abdul Kadir; Cut Zulisna Fonda; Nazariah Nazariah (Prodi Tadris Matematika Universitas Muhammadiyah Aceh, 2021)
Estimation is one part of mathematics that is widely used in everyday life. In learning mathematics, it can be used to control estimation errors and it can facilitate a person's response in getting an answer as well. Therefore, the estimation requires attention to be taught to students properly. This study aimed to describe the estimation profile of junior high school students in solving computational problem based on mathematics ability. This research was conducted at the junior high school students grade VII with 1 person from each level of mathematical ability. Data collection was done by written test and interview. Data analysis consisted of (1) data reduction (2) data display and (3) conclusion / verification. The research results indicate High mathematical ability student understands the subject matter, mentions the information contained on the problem. Estimation strategies that were used in solving computational problems were front-end strategy, the number of special strategy, compatible number strategy and rounding strategy and looking back to the solution. High ability students in solving arithmetic problems only use four estimation strategies.